Influence of Rhythmic Extreme Cooling (â€“120Â°Ð¡) on Functional State of Body in Rats in Their Aging - Martynova, Yuliia V.; Babiichuk, Vladislav G.; Loginova, Olga O. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):159.